Pergerakan Dakwah MUI Dalam Mencegah Penyebaran Aliran Sesat Di Kalangan Remaja Kota Binjai - Mahatir Al Baihaqi; Rubino Rubino (Universitas Cokroaminoto Yogyakarta, 2026)
This qualitative research aims to examine the da'wah movement of the Indonesian Ulema Council (MUI) of Binjai City in East Binjai District in overcoming the spread of deviant sects among teenagers. Based on observation data, interviews, and documentation to analysis, MUI Binjai has carried out da'wah through a community approach, education of ulama cadres, collaboration with the government, and the use of digital media. However, several weaknesses were identified: limited funds, digital media is less than optimal in reaching teenagers, and a continuous evaluation and monitoring system has not been implemented. An inclusive da'wah movement, adaptive to community needs is highly recommended for MUI Binjai. Therefore, these findings contribute theoretically and practically in the development of contemporary institutional da'wah strategies.